Immunohistochemistry Expression Gata3 Based on Subtypes of Ovarian Carcinoma at Haji Adam Malik General Hospital Medan 2019-2021 - Alamanda, Intan Nefia; Betty, Betty; Delyuzar, Delyuzar; Laksmi, Lidya Imelda; Chrestela, Jessy; Soekimin, Soekimin (Majalah Patologi Indonesia, 2024)
Background Ovarian carcinoma is a cancer with high mortality in women and although comprehensive management with surgery and chemotherapy at an advanced stage, the resistance rate is still low. GATA3 contributes to the progression of malignancy and its expression is one of the predictors in some malignancies, but the results are mixed in ovarian carcinoma. High GATA3 expression is associated with the aggressiveness of tumor growth and poor prognosis of ovarian carcinoma.   Methods This research is an cross-sectional descriptive-analytical study with 33 histological specimens diagnosed with ovarian carcinoma from medical records/archives at H. Adam Malik Hospital Medan. Each sample specimen was stain with GATA3, and several various histopathological subtypes of ovarian carcinoma.   Results From a total of 33 samples, 14 samples were serous carcinoma, 6 samples were mucinous carcinoma, 7 samples were endometrioid carcinoma, and 6 samples were clear cell carcinoma. GATA3 was expressed in 42.5% of serous carcinoma. Positive expression of GATA3 is mostly found in advanced ovarian carcinoma, older age, and histopathological type of serous carcinoma.    Conclusion Immunohistochemistry GATA3 expression was expressed in 42.4% of serous carcinoma, 21.2% in endometrioid carcinoma, 18.2% in clear cell carcinoma, and 18.2% in mucinous carcinoma.   Keywords: ovarian carcinoma, GATA3, immunohistochemistry